Pengaruh Kualitas Produk Dan Citra Merek Terhadap Kepuasan Konsumen Kosmetik Y.O.U (Survey Pada Pengunjung Counter Produk Skincare Y.O.U Di Toko Queen Gallery Solok) - Zuraedah Indah; Iyasmadi Iyasmadi; Hane Johan (Journal of Innovative and Creativity, 2026)
This study aims to determine (1) the partial and simultaneous effects of brand image and price on consumer satisfaction with Y.O.U cosmetics skincare products at Queen Gallery Solok Store and (2) the most dominant variables affecting consumer satisfaction with Y.O.U cosmetics skincare products at Queen Gallery Solok Store. This study utilises quantitative data and multiple linear regression analysis, with research data obtained from questionnaires distributed to Y.O.U cosmetics consumers at Queen Gallery Solok Store, involving a sample size of 50 respondents. Based on the research results using the T-test and F-test, it is concluded that (1) The variables of brand image and price have a positive effect, both separately and simultaneously, on the purchase decision of Y.O.U cosmetics skincare products at Queen Gallery Solok Store. (2) The variable that has the most dominant effect on consumer satisfaction with the purchase of Y.O.U cosmetics is brand image.